Synthesis, solubility and antitumor activity of maslinic acid derivatives. - Fuentes-Ríos, David; Cepero, Ana; García-Castro, Miguel; Contreras-Cáceres, Rafael; López-Romero, Juan Manuel; Luque, Cristina; Cabeza, Laura; Melguizo, Consolación; Prados, José (Elsevier, 2022)
Maslinic acid (MA), a pentacyclic triterpenoid obtained from olives that is characterized by its antiproliferative activity in tumor cells, has become a promising molecule that could be modi ed to improve cancer treatment. In this work we have synthesized in good yields several new MA conjugates, including glycerin, oligo(ethylene glycol), and amino acid derivatives (compounds 3a-f). The synthesis offers the possibility of recovering unreacted MA, and thus the scaling up of the process. For the tyramine-MA conjugate, compound 3f or TMA, the preparation has been optimized to a one-pot reaction. Solubility of conjugates in polar solvents has been measured, showing a marked increase of solubility with respect to MA. Moreover, we selected the tyramidyl maslinic acid conjugate (3f or TMA) to determine antitumor capacity over a wide range of cancer cell lines, including glioblastoma, mela- noma, breast, lung, colorectal and pancreatic cancer. Our results clearly demonstrated that TMA induced higher cytotoxicity in all cancer cell types compared to MA. TMA was more effective than MA, especially in breast cancer cells (MCF-7) and melanoma cells (B16–F10) where IC50 reductions of 4.12 and 4.72, respectively, was detected. Interestingly, TMA showed a remarkable antitumor ability against the resistant HCT-15 colon cancer cell line. Furthermore, we demonstrated for the rst time a relevant effect of a MA derivative against glioblastoma cells (A172 and SF-268). These results suggest that TMA is able to improve the antitumor characteristics of MA in a wide range of cancers and that it may be a promising compound for various tumor types, including resistant cancer.
Keywords: Triterpenos; Enlaces químicos; Neurotransmisores; Cáncer; Citotoxicidad por mediación celular; Pentacyclic triterpenes; Chemical conjugates; Tyramine; Resistant cancer; Cytotoxicity